2016
DOI: 10.1159/000447923
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of EMMPRIN and MMP-9 Expression by Epigallocatechin-3-Gallate through 67-kDa Laminin Receptor in PMA-Induced Macrophages

Abstract: Background/Aims: It is well documented that overexpression of EMMPRIN (extracellular matrix metalloproteinase inducer) and MMPs (matrix metalloproteinases) by monocytes/macrophages plays an important role in atherosclerotic plaque rupture. Green tea polyphenol epigallocatechin-3-gallate (EGCG) has a variety of pharmacological properties and exerts cardiovascular protective effects. Recently, the 67-kD laminin receptor (67LR) has been identified as a cell surface receptor of EGCG. The aim of the present study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…MMP-9 production was reduced after inhibition of MEK1/2/ ERK, JNK, P38 and NF-κB, all of which are known to be involved in MMP-9 production in other cell systems [41][42][43]. Our data show that the inhibition of MEK/ERK significantly suppressed the MMP-9 production, suggesting that NF-κB and MAPK signaling pathways may have a key role in MMP-9 regulation.…”
Section: Discussionmentioning
confidence: 54%
“…MMP-9 production was reduced after inhibition of MEK1/2/ ERK, JNK, P38 and NF-κB, all of which are known to be involved in MMP-9 production in other cell systems [41][42][43]. Our data show that the inhibition of MEK/ERK significantly suppressed the MMP-9 production, suggesting that NF-κB and MAPK signaling pathways may have a key role in MMP-9 regulation.…”
Section: Discussionmentioning
confidence: 54%
“…Accumulating evidence has revealed that EGCG, as a potent antioxidative agent, can inhibit inflammation and enhance the survival of disc cells in oxidative stress [31]. The anti-inflammatory effects of EGCG on radiculopathic pain have also been investigated in vitro and may benefit from its inhibitory effect on the overexpression of pro-inflammatory mediators [13, 32]. Given the inhibition of immune cell-derived cellular functions by arsenic exposure and the antioxidative and anti-inflammatory properties of EGCG in antagonizing increased secretion of inflammatory mediators, simultaneous exposure to EGCG has been found to be beneficial in increasing arsenic mobilization and assisting the recovery of altered biochemical levels during chemical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that 67LR expression is not affected by EGCG treatment and that 67LR expression confers EGCG an inhibitory effect on the dysregulated up-regulation of MMP-9 and MCP-1 [20, 22]. Furthermore, numerous studies have shown that EGCG suppresses the expression of TLR4 signalling through binding to the 67LR [18, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that EGCG has a potential anti-inflammatory effect [18, 19] and reduces MMP-9 expression through a cell surface receptor, 67-kDa laminin receptor (67LR) [20]. Recently, it has been confirmed that 67LR is involved in the suppressive effect of EGCG on TLR4 expression in macrophages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation